AYAT DAN HADIS TENTANG DISTRIBUSI - Agustina, Hilda; Primustyawan, Muchamad Arif (STAI YAPIS Takalar, 2023)
Distribution is an important part of creating prosperity for all of its people. Islam demands that its people prioritize morality in carrying out the economy. The goal is to produce conditions of stability in the nation's economy because distribution can influence a nation's economy. The method used in this research uses the library research method, namely research by collecting data and scientific papers related to the object of research discussion or collecting data with a library nature.